Safety and biodistribution of sulfated archaeal glycolipid archaeosomes as vaccine adjuvants. Issue 7 (3rd July 2018) - Akache, Bassel; Stark, Felicity C.; Iqbal, Umar; Chen, Wangxue; Jia, Yimei; Krishnan, Lakshmi; McCluskie, Michael J.
ABSTRACT: Archaeosomes are liposomes comprised of ether lipids derived from various archaea. Unlike conventional ester-linked liposomes, archaeosomes exhibit high pH and thermal stability. As adjuvants, archaeosomes can induce robust, long-lasting humoral and cell-mediated immune responses and enhance protection in murine models of infectious disease and cancer. Archaeosomes constituted with total polar lipids (TPL) of various archaea are relatively complex, comprising >10 different lipid compounds. Archaeosomes can be constituted with semi-synthetic glycerolipids built on ether-linked isoprenoid phytanyl cores with varied synthetic glycol- and amino-head groups. However, such semi-synthetic archaeosomes involve many synthetic steps to arrive at the final desired glycolipid composition. We have developed a novel archaeosome formulation comprising a sulfated saccharide group covalently linked to the free sn-1 hydroxyl backbone of an archaeal core lipid (sulfated S-lactosylarchaeol, SLA) mixed with uncharged glycolipid (lactosylarchaeol, LA). This new class of adjuvants can be easily synthesized and retains strong immunostimulatory activity for induction of cell-mediated immunity following systemic immunization. Herein, we demonstrate the safety of SLA/LA archaeosomes following intramuscular injection to mice and evaluate the immunogenicity, in vivo distribution and cellular uptake of antigen (ovalbumin) encapsulated into SLA/LA archaeosomes. Overall, we have found that semi-synthetic sulfated glycolipid archaeosomes are a safe and effective novel class of adjuvants capable of inducing strong antigen-specific immune responses in mice and protection against subsequent B16 melanoma tumor challenge. A key step in their mechanism of action appears to be the recruitment of immune cells to the injection site and the subsequent trafficking of antigen to local draining lymph nodes.